Measurement of electrons from beauty hadron decays in pp collisions at √s=7 TeV - Abelev, B.; Adam, J.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agócs, A.G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad, N.; Ahmad Masoodi, A.; et al. (Elsevier, 2013)
The production cross section of electrons from semileptonic decays of beauty hadrons was measured at mid-rapidity (|y| < 0.8) in the transverse momentum range 1 < pT < 8 GeV/c with the ALICE experiment at the CERN LHC in pp collisions at a center of mass energy √s = 7 TeV using an integrated luminosity of 2.2 nb−1. Electrons from beauty hadron decays were selected based on the displacement of the decay vertex from the collision vertex. A perturbative QCD calculation agrees with the measurement within uncertainties. The data were extrapolated to the full phase space to determine the total cross section for the production of beauty quark–antiquark pairs.
Keywords: LHC; ALICE experiment; pp collisions; Single electrons; Heavy flavor production; Beauty production; https://purl.org/pe-repo/ocde/ford#1.03.03